Three new species of Culex (Melanoconion) (Diptera: Culicidae) from French Guiana based on morphological and molecular data - Talaga, Stanislas; Gendrin, Mathilde (Zootaxa, 2022)
Culex mosquitoes of the subgenus Melanoconion Theobald, 1903 of the genus Culex Linnaeus, 1758 include numerous species recognized as vectors of viruses affecting humans. This subgenus is the most speciose among the entire mosquito fauna of the Americas. Despite decades of taxonomic research, many species remain undiscovered, especially in the Amazonian biome. In this article, we provide the description of three new species of Culex (Melanoconion) recently discovered in a biological reserve in French Guiana. Culex (Mel.) sallumae n. sp., Cx. (Mel.) hutchingsae n. sp. and Cx. (Mel.) lucakermanni n. sp. are described based on both morphological features of the male genitalia and molecular barcodes obtained from type specimens. Diagnostic characters to assist their identification are provided and their placement within the infrasubgeneric classification of the subgenus Melanoconion is discussed.